2004
DOI: 10.1159/000077117
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Circumcision Status on Periurethral and Glanular Bacterial Flora

Abstract: Introduction: Circumcision is a historical operation which is still performed for different purposes. The aim of this study is to investigate the changes in periurethral and glanular sulcus flora due to circumcision to determine the role of circumcision on urinary tract infections (UTIs). Patients and Methods: Fifty patients who were circumcised for social-religious reasons between January 2000 and January 2001 were evaluated in this prospective study. Two swabs were taken from the periurethral and glanular su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…In an internally controlled study with fair evidence, researchers cultured the periurethral and glandular sulcus of 50 children aged 1 to 12 weeks before and 4 weeks after circumcision and found the pathogenic bacteria largely disappeared after circumcision (33 children had pathogenic bacteria before circumcision and 4 had pathogenic bacteria after circumcision). 26 In adults and children, there is fair evidence that periurethral flora contains fewer pathogens after circumcision than before circumcision. 26,27 Because these studies looked at cultures 1 time (4 weeks after the circumcision), the long-term significance of the findings is unclear.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an internally controlled study with fair evidence, researchers cultured the periurethral and glandular sulcus of 50 children aged 1 to 12 weeks before and 4 weeks after circumcision and found the pathogenic bacteria largely disappeared after circumcision (33 children had pathogenic bacteria before circumcision and 4 had pathogenic bacteria after circumcision). 26 In adults and children, there is fair evidence that periurethral flora contains fewer pathogens after circumcision than before circumcision. 26,27 Because these studies looked at cultures 1 time (4 weeks after the circumcision), the long-term significance of the findings is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…26 In adults and children, there is fair evidence that periurethral flora contains fewer pathogens after circumcision than before circumcision. 26,27 Because these studies looked at cultures 1 time (4 weeks after the circumcision), the long-term significance of the findings is unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 After circumcision, the number of uropathogenic bacteria decreases substantially. 19,21 The risk of uri- 30 ‡Data on the time and day of presentation were collected from the emergency department database using the date and time the patients were seen for triage. Length of stay defined as time between presentation to triage and discharge from the emergency department.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a subset of uncircumcised boys with a poorly visible urethral opening are at increased risk of urinary tract infection, [15][16][17] leading some experts to consider giving children with tight foreskins topical cortisone or circumcision to prevent urinary tract infections. 13,[18][19][20][21] We designed a study to challenge the opinion that all uncircumcised boys are at increased risk for urinary tract infections. We hypothesized a hierarchy of risk among uncircumcised boys depending on the visibility of the urethral meatus, with those with a partially or nonvisible meatus at highest risk, and those with a completely visible meatus having a level of risk similar to that of boys who have been circumcised.…”
mentioning
confidence: 99%